"The Neolithic Cemetery at Tell el-Kerkh" - Tsuneki , Akira (Archaeopress Publishing, 2022)
The Neolithic Cemetery at Tell el-Kerkh is the second volume of the final reports on the excavations at Tell el-Kerkh, northwest Syria. The 12-year field campaigns at Tell el-Kerkh yielded several unexpected archaeological findings. The existence of the oldest cultural deposits from the early Pre-Pottery Neolithic B period (c. 8700-8300 BC) in northwestern Syria was revealed. The investigations also revealed that several large and complex societies had existed from the late Pre-Pottery Neolithic B to the middle Pottery Neolithic periods (c. 7600-6000 BC). One of the most conspicuous findings of the excavations at Tell el-Kerkh was the discovery of a Pottery Neolithic cemetery dating between c. 6400 and 6100 BC, which makes it one of the oldest outdoor communal cemeteries in West Asia. This book focuses specifically on this cemetery. It reports the discovery of over 240 burials and discusses the process of the formation and development of the cemetery. Initially used for traditional house burials in a corner of the settlement, the cemetery eventually became a graveyard that was physically separated from the residential buildings and consisted only of graves. In other words, burials that were deeply related to each house developed into an outdoor communal cemetery of the settlement. The Kerkh Neolithic cemetery was a precursor to the wider development of communal cemeteries in West Asia, and its investigation provides us with a deeper understanding of Neolithic society in West Asia.